Inhibitory Action of 4-n-Butylresorcinol (Rucinol®) on Melanogenesis and Its Skin Whitening Effects - Okubo, Tadashi; Oyobikawa, Midori; Shaku, Masao; Takenouchi, Masaki; Futaki, Kiyoko; Katagiri, Takayuki; Kawai, Mitsuo (Journal of Society of Cosmetic Chemists of Japan, 2001)
We have reasoned that by either enhancing inhibition effectiveness of tyrosinase activity or by inhibiting the activities of both tyrosinase and TRP-1, we should be able to develop more effective whitening cosmetics. We found 4-n-butylresorcinol (BR) to have strong inhibitory effect against melanogenic enzymes which are responsible for hyperpigmentation. BR reversibly inhibited melanin production in B16 mouse melanoma cells without any effects on cell growth, and its potency was stronger than that of arbutin or kojic acid which are widely used in whitening cosmetics. Topical application of 0.3% BR lotion prior or posterior to UVB-irradiation effectively suppressed UVB-induced hyperpigmentation in human. In our extensive consumer usage test involving 449 healthy females, a large proportion of subjects felt there were improvements in conditions of pigmentation, skin darkness, and freckles increased in as little as 1 month. These experimental data indicated that BR is an effective skin whitening agent which can be safely used in cosmetics. Furthermore, a trial to evaluate clinical effects of 0.3% BR lotion in patients with liver spot was made. BR lotion was evaluated as slightly useful or better in 52 (83.9%) out of 62 subjects. Accordingly, we concluded that BR can be used in the clinical treatment of liver spot.